Anatomical, histochemical and phytochemical screening of the vegetative parts of Eichhornia crassipes - Bibi, Mamoona; Asad, Fayaz; Shahid, Sabrina; Kiramat, Haseeba (Journal of Pure and Applied Agriculture, 2023)
Eichhornia crassipes, commonly known as water hyacinth, is a free-floating aquatic plant that is a member of the Pontederiaceae family. Due to its rich phytochemical composition, it can be used in a wide range of medicinal and industrial applications. Hence, the present study attempts to assess the morphological, anatomical, and phytochemical characteristics of Eichhornia crassipes. E. crassipes has kidney-shaped leaves that turn dark green and have several layers including cuticle, epidermis, palisade parenchyma, spongy parenchyma, air cavities, xylem, and phloem. The roots are feathery and dark purple with different layers including root epiblema, upper cortex, middle cortex, lower cortex, pericyclic xylem, phloem, and pith. The bulb also has different layers including epidermis, outer cortex, cells with crystal, air space, xylem, and phloem. Stomata are present on both sides of the leaf and quantitative phytochemical analysis shows the presence of various secondary metabolites with the highest quantity of alkaloids in the root and the highest quantity of tannin and flavonoid in the leaf. E. crassipes has unique anatomical features such as kidney-shaped leaves with a dark green color and various tissues like cuticle, epidermis, palisade parenchyma, and spongy parenchyma. The roots have a dark purple appearance with different tissue layers, while the bulb has the epidermis, outer cortex, cells with crystals, and phloem tissue. The plant's leaves have stomata on both sides and contain alkaloids in the root and tannins and flavonoids in the leaf. Further, research is recommended to examine this plant more pharmacognostically for various disorders.